Modular thermoelectric conversion system for low-temperature thermal energy - Neska Mirosław; Mrozek Mirosław; Majcher Andrzej (E3S Web of Conferences)
Dwindling fossil fuel resources and the drive to create a closed-loop economy in technological systems are forcing the development of systems managing low-temperature waste heat. This paper presents a system equipped with thermoelectric cells that convert heat into electricity. The prototype system comprises individual MTEG modules and a DC-AC power converter. The MTEG module is a sandwich-like layered structure. The core of the MTEG module consists of twenty TEG thermoelectric elements, with liquid heat exchangers positioned on the hot and cold sides of the TEGs, respectively. The paper presents the results of the verification and validation of the system. The results, which demonstrate the high efficiency of the exchangers and the converter and the flexibility to combine and expand, with the goal to maximise the use of available low-temperature heat. The solution exhibits an energy conversion efficiency of a few per cent, primarily attributable to the low efficiency of the TEGs. However, in numerous industrial applications, it can enhance the exergy of ongoing processes, where substantial amounts of low-temperature heat are dissipated.